Konsep Kebahagiaan Erbe Sentanu dan Martin Seligman (Erbe Sentanu and Martin Seligman's Concept of Happiness) - Naivatul, Ulya Nabilah; Nailatin, Fauziyah; Hamim, Rosyidi (Happiness: Journal of Psychology and Islamic Science, 2024)
Happiness is a fundamental aspect of human life. Everyone desires a happy, meaningful, and satisfying life. However, many people misunderstand the true nature of happiness, leading them to seek it in the wrong ways. In the modern era, many people perceive happiness as being materialistic, leading to a hedonistic attitude. Certainly, this can also have negative consequences. Therefore, the author attempts to elucidate the concept of happiness from the perspectives of the proponents of sincere quantum and positive psychology, Erbe Sentanu and Martin Seligman. The main focus of this research is how the concept of happiness is explained by Erbe Sentanu and Martin Seligman? What are the comparisons between their concepts of happiness? This research utilizes the method of library research accompanied by an interview with Erbe Sentanu. The results of the research reveal similarities and differences in the explanations of happiness concepts from both figures. Undoubtedly, both figures have distinctive emphases in explaining happiness. The implication is that the concept of happiness shows both similarities and differences in the explanations of the two figures studied, with each figure offering a unique emphasis that can enrich the philosophical discourse on happiness.